Hardware Implementation of Random Number Generators - Wijesinghe, W.A.S.; Jayananda, M.K.; Sonnadara, D.U.J. (My University, 2006)
Random numbers are used in a wide variety of applications. True random number generators are slow and expensive for many applications while pseudo random number generators (RNG) suffice for most applications. Although a majority of random number generators have been implemented in software level, increasing demand exists for hardware implementation due to the advent of faster and high density Field Programmable Gate Arrays (FPGA). FPGAs make it possible to implement complex systems, such as numerical calculations, genetic programs, simulation algorithms etc., at hardware level. This paper discusses in detail the hardware implementation of several RNGs and their characteristics. Somewhat complex Cellular Automata based RNGs show slightly improved performance compared to the simplest Linear Feedback Shift Register RNG.
Keywords: Random numbers; FPGA